Distribution of Zakat towards Poverty Alleviation - Azrai, Azrai; Harahap, M. Guffar; Haidir, Haidir; Saragih, Alkausar (Innovative: Journal Of Social Science Research, 2024)
This research aims to investigate the impact of zakat distribution on poverty alleviation efforts in Medan City. By focusing on the role of zakat in helping vulnerable community groups, this research investigates the extent to which zakat distribution can make a positive contribution to reducing poverty levels in this city. The research method involves quantitative and qualitative data analysis, including surveys and interviews with zakat recipients, zakat management institutions, and related stakeholders. The research findings provide in-depth insight into the effectiveness of zakat distribution in providing assistance to community groups in need. The results of data analysis show that zakat distribution can have a positive impact on poverty alleviation in several areas in Medan City. However, several challenges were also found, including unequal distribution and lack of transparency in the zakat distribution mechanism. Apart from that, public awareness about zakat and understanding regarding the management of zakat funds also play an important role in the effectiveness of distribution. Therefore, recommendations have been prepared to increase transparency, public awareness and supervision in an effort to increase the effectiveness of zakat distribution as an instrument for poverty alleviation in Medan City. It is hoped that this research can provide a basis for zakat management institutions, the government and the community to optimize the role of zakat in efforts to reduce poverty levels in Medan City, as well as contribute to further understanding of the dynamics of zakat distribution and its impact on community welfare.